Design and analysis of receiver filters for multiple chip-rate DS-CDMA systems. - Srinivasan, R.
As multimedia applications proliferate, there is a desire to provide wireless transport to information streams with inherently different data rates. Direct-sequence code division multiple access (DS-CDMA) is a natural multiple-access strategy for multiple data-rate systems. Previous work on multirate DS-CDMA receivers has focused on signal-processing techniques, which detect all users of all rates simultaneously. In the current work, multirate users have multiple bandwidths. Thus, it is proposed to exploit bandwidth differences to achieve frequency-based rate separation followed by single-rate detection schemes. Such a methodology enables a tradeoff between receiver complexity and performance. The performance of the proposed filters and receivers are derived for both a modified matched filter and modified decorrelator employing rate separation. The performance of a multirate CDMA overlay system is evaluated. In addition, chip pulse shaping for wide-band users is developed to improve performance for narrow-band users for the overlay system
Keywords: PCS; Wiener filters; Bandwidth; Cellular communication systems; Chip pulse shaping; Data rates; Direct-sequence code division multiple access; Frequency-based rate separation; High-pass filters; Information streams; Interference suppression; Low-pass filters; Modified decorrelator; Modified matched filter; Multimedia applications; Multiple chip-rate DS-CDMA systems; Multiple data-rate systems; Multirate CDMA overlay system; Multirate DS-CDMA receivers; Narrow-band users; Performance evaluation; Personal communication systems; Rate separation; Receiver complexity; Receiver filter analysis; Receiver filter design; Signal processing techniques; Single-rate detection; Wide-band users; Wireless transport